(untitled) (Marketing Journal, 2025)
This article examines the current state and development prospects of the profession of guide -interpreters in Uzbekistan. It explores the essential role of guide - interpreters in the tourism sector as cultural mediators and communicators who enhance tourist experiences and foster cross -cultural understanding. The study analyzes the skills, education, and working conditions required for the profession, and employs a SWOT analysis to assess its strengths, weaknesses, opportunities, and threats. The findings emp hasize the need for continuous professional development and technological adaptation to ensure competitiveness in the global tourism market.